Optimalisasi Program KKN V Mahasiswi STIBA Makassar sebagai Upaya Pembinaan Berbasis Religi di Kelurahan Moncongloe Lappara - Kurnaemi Anita; Musriwan Musriwan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
The purpose of implementing this KKN is to provide religious guidance to the local community. The method of implementing the Community Service Program begins with observing the condition of the community using SOAR analysis adjusted to the moment of the month of Ramadan which then resulted in several programs including:(1) Teaching the Qur'an with the Dirosa method; (2) TPA development; (3)10 days of memorizing the Qur'an; (4) Taklim Muslimah Weekly; and (5) Training of the corpse execution. All of these programs were warmly and enthusiastically welcomed by the local community and succeeded in bringing about the desired changes. So that even though the KKN has ended, there is a change in the attitudes and behavior of people who are more religious, as well as the ability to read the Qur'an is getting better.